2021
DOI: 10.1186/s43170-021-00045-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adoption and intensity of improved faba bean cultivars in the central highlands of Ethiopia: a double-hurdle approach

Abstract: Background Faba bean (Vicia faba. L) is the most important pulse crop both in area coverage and volume of annual production in Ethiopia. However, productivity in terms of yield in Ethiopia is still far below its potential. One important reason is that farmers are largely dependent on their local landraces. Despite the release of about 34 improved faba bean cultivars, farmers’ use of certified improved seeds is very low. This study, therefore, aimed to generate useful information on farmers’ ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…This is because farmers are aware of the recently developed agricultural technologies; they are familiar with the production techniques and advantages of the technologies, which helps them overcome their fear and form a favorable opinion of them. This result was consistent with the theoretical model of diffusion of innovation as well as earlier empirical research [ 53 , 69 ]. The diffusion of innovation suggested that information dissemination speeds up the adoption of agricultural technologies through the creation of awareness and knowledge among smallholder farmers.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is because farmers are aware of the recently developed agricultural technologies; they are familiar with the production techniques and advantages of the technologies, which helps them overcome their fear and form a favorable opinion of them. This result was consistent with the theoretical model of diffusion of innovation as well as earlier empirical research [ 53 , 69 ]. The diffusion of innovation suggested that information dissemination speeds up the adoption of agricultural technologies through the creation of awareness and knowledge among smallholder farmers.…”
Section: Resultssupporting
confidence: 93%
“…[ 43 ] on the desire for durable items and [ 51 ] on the use of fertilizer showed that such choices might not be closely related. Recently, most researchers [ [52] , [53] , [54] , [55] , [56] , [57] , [58] ] used the Double Hurdle mode for estimating the adoption decision and intensity of the use of agricultural technologies. As a result, the Double Hurdle model was used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The study concluded that high initial costs posed a significant limitation and that characteristics of the cultivation area, household size, and access to extension services were decisive factors in implementing a certification (Kassa et al, 2021).…”
Section: Marketingmentioning
confidence: 99%
“…Its export has increased from time to time, but the region's contribution is not as significant as its potential [ 22 , 30 ]. Key challenges of mung bean production in the region is concerned, it is unknown to most farmers due to low genetic biodiversity and low proportion of improved genotypes [ 30 , 31 ]. The productivity is low due to multifaceted risk factors those have not been addressed fully by farmers and other stakeholders [ 26 ].…”
Section: Introductionmentioning
confidence: 99%